Investigation of chemical etching on flow in channel - Tan, Ming Yong (Nanyang Technological University, 2021)
Fluids can be found in many aspects of industrial engineering applications, and frictional losses in fluid flows are a common occurrence. This is undesirable as energy is lost due to these frictional losses. As a result, more energy is required to transport the fluids, driving up operation costs of these engineering applications. Several research studies have shown that superhydrophobic surfaces have favourable microstructures which helps in reducing frictional loss in fluid flows. While there are different fabrication methods available in the market, chemical etching is one of the simpler and cheaper methods to fabricate superhydrophobic surfaces. To obtain superhydrophobic surfaces using chemical etching, a surface needs to be immersed in chemical agents first before using a suitable agent to lower its surface energy. A two-step chemical etching process was adopted in this study for fabricating the superhydrophobic surfaces. The Aluminium Alloy 6061 material is selected for the etching process as it is widely used in fluid flow applications. A preliminary experiment was first done to obtain the optimum combination of concentration and etching duration to fabricate superhydrophobic surface. The hydrophobicity of the surface is characterised by its contact angle, surface morphology and surface roughness. Selected parameters were then used to fabricate large samples to conduct pressure drop experiments to establish a relationship between hydrophobic levels and frictional losses. These samples were then submerged for 2 days to find out if these fabricated samples are able to retain its superhydrophobic properties. From the experimental results, a two-step etching process of 2M NaOH for 2.5min followed by 0.5M NaOH for 6min at elevated temperatures produced a superhydrophobic surface with a contact angle approximately 156°. The interstices between the peaks and valleys of the microstructure allows more air bubble to be trapped, reducing the wettability of the surface. While the two-step chemical etching process is low cost and a simpler method to produce superhydrophobic surfaces, more research needs to be done on retention of its superhydrophobic properties for this method to be potentially applicable to industrial engineering applications.